An Analysis of Transitivity in the Song Lyrics from the Album 'Hotel California' - Lutfianto, Mochamad Rizal; , Dra. Malikatul Laila M.Hum (2017)
AN ANALYSIS OF TRANSITIVITY IN THE SONG LYRICS FROM THE ALBUM 'HOTEL CALIFORNIA' ABSTRACT MOCHAMAD RIZAL LUTFIANTO. A320130058. AN ANALYSIS OF TRANSITIVITY IN THE SONG LYRICS FROM THE ALBUM 'HOTEL CALIFORNIA'. Research Paper. School of Teacher Training and Education. Muhammadiyah University of Surakarta. 2017. This study is an analysis of transitivity in the song lyrics from the album 'Hotel California' based on the lexicogrammar and context in the framework of functional grammar. This study is aimed to identify the elements of the song lyrics based on its transitivity and to explain the realization of ideational meanings in the song lyrics. This research is used descriptive qualitative type of the study to examine the problem. The writer uses documentation in the technique of collecting data. The writer finds 60 clauses in song lyrics. In analyzing the data, the writer uses lexicogrammar of the functional grammar patterns to answer the first problem. Furthermore, the writer refers to the context of functional grammar to answer the second problem. From the analysis result, the writer finds three kinds elements of transitivity. Those are participants, processes, and circumstances. There are 14 types of participants, namely actor, goal, senser, phenomenon, behaver, token, value, carrier, attribute, sayer, receiver, verbiage, existent, and client. The most dominant participant is material's participants that are actor and goal. It implies that the composer is often the doing physically process in the journey. Moreover, the writer also finds seven types of processes, namely material process, relational process, mental process, verbal process, behavioural process, existential process, meteorogical process. From the process found in the analysis, material process has the most dominant frequency. It indicates that the composer would like to show the journey experience. The last elements found are circumstance. Those are circumstances of location, extent, manners, cause, and contingency. The dominant circumstance is circumstance of location. By using the circumstance of location, it indicates that the composer wants to give the clear information about the setting of the process happened. Keywords: Functional grammar, song lyrics, ideational meaning, transitivity, participants, process, and circumstance.